Bioorthogonal Uncaging of the Active Metabolite of Irinotecan by Palladium‐Functionalized Microdevices. Issue 63 (8th November 2018) - Adam, Catherine; Pérez‐López, Ana M.; Hamilton, Lloyd; Rubio‐Ruiz, Belén; Bray, Thomas L.; Sieger, Dirk; Brennan, Paul M.; Unciti‐Broceta, Asier
Abstract: SN‐38, the active metabolite of irinotecan, is released upon liver hydrolysis to mediate potent antitumor activity. Systemic exposure to SN‐38, however, also leads to serious side effects. To reduce systemic toxicity by controlling where and when SN‐38 is generated, a new prodrug was specifically designed to be metabolically stable and undergo rapid palladium‐mediated activation. Blocking the phenolic OH of SN‐38 with a 2, 6‐bis(propargyloxy)benzyl group led to significant reduction of cytotoxic activity (up to 44‐fold). Anticancer properties were swiftly restored in the presence of heterogeneous palladium (Pd) catalysts to kill colorectal cancer and glioma cells, proving the efficacy of this novel masking strategy for aromatic hydroxyls. Combination with a Pd‐activated 5FU prodrug augmented the antiproliferative potency of the treatment, while displaying no activity in the absence of the Pd source, which illustrates the benefit of achieving controlled release of multiple approved therapeutics—sequentially or simultaneously—by the same bioorthogonal catalyst to increase anticancer activity. Abstract : Palladium‐functionalized microdevices were used to uncage newly developed prodrug that releases SN‐38 (irinotecan′s active metabolite) in combination with previously known anticancer prodrug of 5FU.